PHARMACOGENETIC FEATURES OF THERAPY OF PATIENTS WITH ATHEROSCLEROSIS - A. L. Khokhlov; A. N. Yavorsky; N. O. Pozdnyakov; J. V. Rybachkova; E. S. Emelianov; A. A. Khokhlov; A. E. Miroshnikov; S. O. Pozdnyakov (Архивъ внутренней медицины, 2018)
The complexity of therapy of lipid metabolism disorders is not only in comorbidity and polypragmasia, but also in predicting a genetically determined response to the treatment. The aim of our work was to  study the pharmacogenetics features of pharmacotherapy of patients with non-alcoholic fatty liver disease, with various forms of IHD, and  patients taking statins. We investigated 4 study groups: I — 60  patients with 2 type of diabetes and non-alcoholic fatty liver disease  (APOE polymorphism); II — 187 patients with IHD (eNOS, AGTR2,  CYP2D6 polymorphisms); III — 111 people with AH and CHF  (polymorphisms: AGT: 704 (Met235Thr), AGT:521 (Thr174Met),  AGTR1: 1166, AGTR2: 1675, CYP11B2: -344, GNB3: 825, ADD1:  1378 (Gly460Trp), NOS3: -786); IV — 62 patients taking  atorvastatin (SLCO1B1*5 polymorphism). Patients with E2, E4 alleles of the APOE gene, taking essential phospholipids, improved  parameters of total cholesterol, HDL, LDL, CA, AP; patients with E3 alleles had a positive dynamics of cholesterol, HDL, TG, LDL, VLDL, CA, urea. Patients having “slow” allelic variants of the gene CYP2D6*10, CYP2D6*4 had received metoprolol, had greater  decrease in heart rate: 1.6 times for CYP2D6*10, 1.7 — for  CYP2D6*4. Earlier debut of IHD is noted in patients with TT variants  of the eNOS gene comparing the patients with GG and GT variants.  Dosages of perindopril depend on AGTR2 gene polymorphisms. The  prevalence of polymorphisms AGTR2: 1675, CYP11B2: -344, NOS3: -786, AGT: 704, GNB3: 825 increases with the increase in the stage of CHF. The parameters of intracardiac hemodynamics in patients  with CHF are associated with AGT: 704, NOS3:-786, GNB3: 825,  ADD1: 1378, AGT: 521 polymorphisms. Allele C of the SLCO1B1*5  gene is associated with an additional risk of statin-induced  myopathy. So the treatment of diseases associated with  atherosclerosis, needs using of a personalized approach for more  effective and safe therapy.